Transformation of Rural Space under the Impact of Tourism: The Case of Xiamen, China - Jinkun Yang; Haitao Ma; Lisheng Weng (Land, 2022)
Tourism plays a key role in sustaining economic development. Previous research has established the connections between tourism and urban growth, as well as the influence of tourism on population and social structure, and the impact of tourism on the landscape. Fewer studies have been conducted on the impact of tourism on the process of rural development change, especially how rural spatial transformation and local community development are driven through tourism. This paper investigates the link between tourism and rural spatial development in China, using in-depth interviews. The research demonstrates that the ambiguity of collective land ownership in China is a key factor in the process of village development. The transformation of villages from “production space” to “consumption space” is driven by tourism based on the land institution arrangement. It is hoped that this research will contribute to a deeper understanding that tourism should be valued in the future as part of the village development process, especially when tourism plays a long-term role in promoting village development.